Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada Masa Pandemi Covid-19 Dengan Kepercayaan Pelanggan Sebagai Variabel Intervening - Rin Rin Riyanti; Kokom Komariah; Erry Sunarya (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The research was aimed atdeterminating Influences service quality toward customer loyalty during the Covid-19 pandemic with case Studies to Matahari Departement Store Costumers of Sukabumi City throgh the mediation of Costumer Trust. The research method used in the research was descriptive and associative with purposive sampling technique in which questionnaires were distributed to 400 respondents who were the customers of Matahari Department Store of Sukabumi City. The technique of analyzing data applied by the researcher was Structural Equation Modelling (SEM) with the help of data tabulating software IBM SPSS AMOS 24. The results of the research show that service quality influence positively and significantly toward customer trust customer trust influences positively and significantly toward customer loyalty, and customer trust mediates the relationship between service quality with customer loyalty. Keywords: Service Quality, Customer Trust, Customer Loyalty